Tritium release performance of neutron-irradiated core–shell Li2TiO3-Li4SiO4 pebbles - Shouxi Gu; Qiang Qi; Fei Sun; Yingchun Zhang; Yasuhisa Oya; Hai-Shan Zhou; Guang-Nan Luo (Nuclear Materials and Energy, 2025)
To enhance the mechanical strength of Li4SiO4 and reduce its sensitivity to carbon dioxide and water, advanced tritium breeder core–shell Li2TiO3-Li4SiO4 was designed and fabricated by graphite bed method. The 1:1 phase ratio between Li2TiO3 and Li4SiO4 was confirmed by X-ray diffraction (XRD) and Rietveld refinement. Scanning electron microscopy (SEM) revealed that submicron-sized Li2TiO3 grains aggregated at the grain boundaries of Li4SiO4. Micro-computed tomography (Micro-CT) distinctly illustrated the shell-structure and the three-dimensional distribution of internal pores, aligning with the original design requirements and expectations. Neutron irradiation and out-of-pile tritium release experiments were conducted to evaluate the tritium release performance. Temperature-programmed desorption tritium release spectra exhibited two distinct release peaks, occurring at approximately 312 and 478 °C. The corresponding desorption activation energies were calculated using varying heating rates, yielding values of 0.63 eV and 1.64 eV, respectively. Isothermal desorption experiments indicated that complete release of residual tritium can be achieved at temperatures exceeding 400 °C. The tritium release rate-controlling process was found to be primarily diffusion of tritium through the crystal, with an effective diffusivity of 3.73 × 10-6exp(−1.35 eV/kT) m2/s.